TEMPO/NBu4Br-Catalyzed Selective Alcohol Oxidation with Periodic Acid - Attoui, Mariam; Vatèle, Jean-Michel (Synlett, 2014)
Oxidation of primary and secondary alcohols, using catalytic amounts of TEMPO and tetra-n-butylammonium bromide in combination with periodic acid and wet alumina in dichloromethane is described. This oxidizing system is compatible with a broad range of functional groups and acid-sensitive protecting groups. Chemoselective oxidation of secondary alcohols in the presence of primary alcohols was observed.
Keywords: alcohols; chemoselectivity; oxidation; periodic acid; TEMPO